A new transmissometer method that measures runway visibility across a short distance - Mariam Mohamed Abud (International Journal of Advances in Applied Sciences, 2023)
The present technique developed a transmissometer idea for intensity measurements in the ecosystem across an 80 cm distance. The method relies on the transmission of an optical or infrared (diode laser 785 nm) signal obtained on spectrum analyses (ocean optics HG4000) received signal from the laser under unique conditions (light dust, heavy dust, and waterdrops) at a short distance. Thus, this approach is useful to measure the intensities of the laser beam and locate the visibility measurements of laser transmissometers in the rain and special care to the dust. The results showed that heavy dust enhanced the visibility measurements for distinct intensity distributions between showers and dust. Since light and heavy dust within a single transmittance can easily cover the entire runway visual range (RVR) range for a brief period, visibility measurements were crucial. The full-scale value corresponds to infinite visibility for heavy dust (0.8611) and minimum visibility for drop rain conditions (0.01073).